Association Between Weekend Catch-Up Sleep and Metabolic Syndrome with Sleep Restriction in Korean Adults: A Cross-Sectional Study Using KNHANES - Son, Soo Min (Diabetes Metab Syndr Obes, 2020)
BACKGROUND: Many researchers have identified that adequate sleep duration is linked to the quality of life and metabolic diseases. Nowadays, it is hard to take enough sleep, so weekend catch-up sleep (CUS) may be an alternative option in modern society. To our knowledge, no previous studies reported the association between weekend CUS and metabolic syndrome, especially in the Korean population. OBJECTIVE: We investigated the association between weekend CUS and the prevalence of metabolic syndrome in Korean adults (≥20 years old) with less than 6 hours of average weekday sleep. PATIENTS AND METHODS: A total of 1,453 individuals were selected from the Korean National Health and Nutrition Examination Survey. Weekend CUS was divided into four categories: ≤0 hour, 0–1 hour, 1–2 hours, and ≥2 hours. Odds ratios (ORs) with 95% confidence intervals (CIs) were derived by univariate and multivariate logistic regression analyses. RESULTS: Participants with weekend CUS ≥1 hour had decreased risk of metabolic syndrome in univariate analysis (CUS 1–2 hours: OR: 0.413, 95% CI: 0.301–0.568; CUS ≥2 hours: OR: 0.382, 95% CI 0.296–0.493). Weekend CUS 1–2 hours reduced the risk of metabolic syndrome in multivariate logistic regression analysis (OR: 0.552, 95% CI: 0.369–0.823). Based on the age group analysis, weekend CUS ≥1 hour reduced the metabolic syndrome among those aged 20–39 and 40–65 (20–39: CUS 1–2 hours OR: 0.248, 95% CI: 0.078–0.783, CUS ≥2 hours OR: 0.374, 95% CI: 0.141–0.991; 40–65: CUS 1–2 hours OR: 0.507, 95% CI 0.309–0.832 CUS ≥2 hours OR: 0.638, 95% CI: 0.415–0.981). CONCLUSION: Weekend CUS was associated with a low risk of metabolic syndrome among Korean adults with sleep restriction.